Effect of Variety and Dosage of Pearl NPK Fertilizer on Growth and Yield of Hybrid Red Chili - Reza Firdaus; Boy Riza Juanda; Iswahyudi Iswahyudi (University of Prof. Dr. Hazairin, SH, 2021)
This study aims to see the growth and yield of hybrid red chili with various varieties and the dose of NPK Mutiara fertilizer and to see the interaction between hybrid red chili varieties and the dose of NPK Mutiara fertilizer. This study used a factorial randomized block design (RAK) consisting of 2 factors, namely the red chili variety factor (V) which consisted of 3 types: V1 = Kastilo F1, V2 = Laju F1, and V3 = Lado F1. The combination factor of NPK fertilizer (P) consisted of 3 levels: P1 = 19 g/plant, P2 = 23 g/plant, and P3 = 28 g/plant. Parameters observed included flowering age (Days), stem diameter (cm), number of chilies per plant (fruit), chili length (cm), chili diameter (cm), fresh chili weight per plant (gr), and fresh fruit weight. per plot (gr). The results showed that hybrid red chili varieties had a significant effect on the parameters of the number of chilies per plant, the weight of fresh chilies per plant, and the weight of fresh chilies per plot. The best results were obtained in the V2 treatment (F1 Laju). The dose of NPK Mutiara had a significant effect on the parameters of flowering age and chili length. The best results were obtained in the P3 treatment (28 g/plant). The interaction of hybrid red chili varieties with NPK Mutiara fertilizer had a significant effect on chili length parameters and the number of chili peppers per plant. However, it had no significant effect on flowering age, stem diameter, chili diameter, fresh chili weight per plant, and fresh chili weight per plot. The best interaction was found in the V2P3 treatment (F1 rate + 28 g/plant).